MAKNA NASIONALISME PADA DIRI GEN Z DALAM BEKERJA DI LUAR NEGERI - Daniel Faran Krisdianto; Eka Yusup; Ema Ema (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2025)
This study aims to understand how Indonesian Generation Z (Gen Z) migrant workers in Japan construct the meaning of nationalism through their subjective experiences of living and working abroad. Using Alfred Schutz’s phenomenological approach and the social construction theory by Peter L. Berger and Thomas Luckmann, this research explores how nationalism is interpreted in the context of transnational life. The study employed a qualitative method with a phenomenological design and collected data through in-depth interviews with three Indonesian citizens aged 19–27 who had worked in Japan for at least one year. The findings reveal that nationalism is perceived in varied ways by the informants. Some view nationalism as an internalized pride and love for the homeland, expressed through cultural preservation efforts such as promoting Indonesian cuisine and traditional attire like batik. Others experience a declining sense of nationalism due to dissatisfaction with social and political conditions in Indonesia. This study affirms that nationalism is not a fixed or geographically bound concept, but a dynamic construction shaped by individual experiences, social interactions, and cultural reflections in a global context.